EFFECTIVENESS OF EXPRESSIVE WRITING THERAPY ON PUBLIC SPEAKING ANXIETY AND PUBLIC SPEAKING SELF-EFFICACY IN STUDENTS OF PSYCHOLOGY STUDY PROGRAM IN BUANA PERJUANGAN KARAWANG UNIVERSITY - Rohayati, Nita; Rahayu, Puspa; Rahman, Utami; Simatupang, Ervina (International Journal of Psychosocial Rehabilitation, 2020)
An increase in public speaking self-efficacy should be done by students of psychology that following the competency level will bring a lot of public speaking. Expressive writing therapy is a therapy that uses the activity of writing as a means to reflect the deepest thoughts and feelings from the grave a hard inflicted trauma). The experimental work on this expressive writing therapy done either in groups and is playing therapy to help the subject develop more adequate insights about yourself and the situation the presentation, improve self-esteem, develop better-coping skills, as well as a means for release tension. This study aims to test the influence of expressive writing therapy against public speaking anxiety and public speaking students in the context of self-efficacy in class. The subject of this study is students that have the anxiety level on public speaking who are considered to be higher until a very high level. Scale compiled based components anxiety speaking in advance general of Rogers (2003), which consists of the components of physical, mental and emotional. The scale of public speaking self-efficacy compiled based on a scale that was developed by Warren (2011) refers to the Selnow (2009) were grouped into the four dimensions include content, structure, delivery and presentational Aids to the audience. This research is using a quasi-experiment with the design of one group before-after design or one group pre-test – post-test design. Subjects received expressive writing therapy treatment for 5 sessions with a duration of 90-120 minutes for each session. The results of the analysis of the quantitative Mann-Whitney and Wilcoxon Signed-Rank Test showed that there is a decrease in the significant level of public speaking anxiety group experiment after treatment expressive writing therapy. Based on the analysis of the qualitative to the results of observation, interviews, and questionnaires concluded the improvement of public speaking self-efficacy. And decreased levels of public speaking anxiety.